Train the Trainer: Using an AI Teacher to Upskill Teachers in India (SciComm Report, 2025)
This study explores the effectiveness of utilising an autonomous AI teacher, represented through an avatar, in enhancing the skills and upskilling existing teachers in India. Focused on nursery-level teaching methods and curriculum development, the research employed a specialised generative AI language model, OIMISA7B, with a 7-billion parameter setup designed specifically for educational delivery. The AI avatar, designed to resemble a female trainer, delivered a series of four lessons, each approximately one hour in length. The study assessed the efficacy of this innovative teaching approach through monitoring programme completion rates, and tracking inquiries made to the AI for further clarifications and doubts. The core focus of the paper is to go beyond directly AI-enabled teaching for students which the researchers have conducted several times before, and instead look at empowering the ecosystem, in this case training the teachers.
Keywords: AI in education; AI; Generative AI; Machine Learning; Teacher Training; Education